2018
DOI: 10.4143/crt.2017.438
|View full text |Cite
|
Sign up to set email alerts
|

Phase II Study of Dovitinib in Patients with Castration-Resistant Prostate Cancer (KCSG-GU11-05)

Abstract: PurposeFibroblast growth factor (FGF) signals are important in carcinogenesis and progression of prostate cancer. Dovitinib is an oral, pan-class inhibitor of vascular endothelial growth factor receptor (VEGFR), platelet-derived growth factor receptor, and fibroblast growth factor receptor (FGFR). We evaluated the efficacy and toxicity of dovitinib in men with metastatic castration resistant prostate cancer (mCRPC).Materials and MethodsThis study was a single-arm, phase II, open-label, multicenter trial of dov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 28 publications
1
17
0
1
Order By: Relevance
“…Dovitinib is an FGF receptor kinase inhibitor which additionally blocks other receptors. A phase 2 study in mCRPC showed only limited efficacy [ 72 ].…”
Section: Treatment Options and Potential Novel Therapiesmentioning
confidence: 99%
“…Dovitinib is an FGF receptor kinase inhibitor which additionally blocks other receptors. A phase 2 study in mCRPC showed only limited efficacy [ 72 ].…”
Section: Treatment Options and Potential Novel Therapiesmentioning
confidence: 99%
“…As the role of stroma in the growth of tumour has become more apparent, the interest in development of therapies that target stroma instead of tumour has grown 25,26 . For example, studies on antibodies against fibroblast growth factor, a signalling molecule for CAFs 27 , antibodies against transforming growth factor beta, a tumor growth enhancing factor produced by CAFs 28 , and T-cell immunotherapies targeting the stroma 29,30 are currently being developed in preclinical settings. While therapies targeting the stroma have not yet reached clinical use, they might become important in the future.…”
Section: Discussionmentioning
confidence: 99%
“…It will be of interest to compare FGFR3-L and FGFR3-S in terms of dimer structure, receptor orientation, transmembrane separation, conformation sampling, and monomer versus dimer status in future studies. Dovitinib is a multi-target RTK SMI that has shown antitumor activity in preclinical and clinical models of solid tumors, including prostate cancer (41)(42)(43)(44). While dovitinib failed a critical phase III trial in metastatic renal cell carcinoma, recent efforts have been taken to identify and select potential responders (e.g., patients with driver FGFR alterations) in future clinical trials.…”
Section: Discussionmentioning
confidence: 99%